Is one‐line hybrid rice coming?. Issue 8 (12th August 2019) - Hu, Xingming; Wang, Fanmiao; Matsuoka, Makoto
Abstract : Hybrid rice proved to be high‐yielding and is of great importance to food safety worldwide. By using gene editing techniques, we generated one‐line hybrid rice by preventing meiosis from occurring, which can largely contribute to maintaining the hybrid dominance.